2014
DOI: 10.1007/s12639-014-0527-2
|View full text |Cite
|
Sign up to set email alerts
|

Sero-prevalence of Haemonchus contortus infection in sheep by Indirect-ELISA using somatic antigen

Abstract: The present work was carried out to study the sero-prevalence of Haemonchus contortus infection in sheep by Indirect-Enzyme Linked Immuno Sorbent Assay (Indirect-ELISA) using somatic antigen. Out of 100 abomasums screened, 57 found positive for H. contortus adult worms. A total of 250 serum samples which includes, 100 serum samples from local abattoir in and around shimoga region from the animals from which the abomasums were collected and 150 serum samples from migratory sheep were used to detect the circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
0
11
2
Order By: Relevance
“…Previously, combined use of ELISA and immunoblotting has been reported as a powerful tool to immuno-diagnose different infections [38,41]. In this study, rHc-CS indirect-ELISA showed higher diagnostic specificity and sensitivity as compared to somatic antigen-based indirect-ELISA format reported in previous study [20]. This contrast might be due to higher binding efficiency of rHc-CS antigen, as type of diagnostic antigens used in study may influence specificity, sensitivity and cross reactivity of assay [42].…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Previously, combined use of ELISA and immunoblotting has been reported as a powerful tool to immuno-diagnose different infections [38,41]. In this study, rHc-CS indirect-ELISA showed higher diagnostic specificity and sensitivity as compared to somatic antigen-based indirect-ELISA format reported in previous study [20]. This contrast might be due to higher binding efficiency of rHc-CS antigen, as type of diagnostic antigens used in study may influence specificity, sensitivity and cross reactivity of assay [42].…”
Section: Discussionmentioning
confidence: 55%
“…Recently, larval antigen, somatic antigens and crude antigen have been evaluated for the immunodiagnosis of H. contortus infection [20,26,27]. However, the specificity and sensitivity is compromised for these antigens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antigen preparations used in diagnostic assays were primarily derived from whole worm extract, excretory and secretory worm products, sonicated egg antigens, partially purified fractions, and recombinant antigens [21]. The crude somatic antigen was evaluated for the immunodiagnosis of H. contortus infection [22]. However, cross-reactions between low sensitivity and different worms limited the use of these antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Several diagnostic assays such as immunoblotting and ELISA based on somatic antigens, crude protein and ES antigen have been described previously to detect H. contortus specific antibodies [4,[15][16][17]. Although, shared antigenic composition which leads to cross-reactivity in diagnosis of H. contortus infection is major disadvantage of these tools [18].…”
Section: Introductionmentioning
confidence: 99%